The counter-cyclical role of remittances in Algeria’s economic resilience a time series analysis (1970-2023) - Boussalem, Soufiane; Bouziane, Mohammed (International journal of economic perspectives, 2025)
This study explores whether remittance transfers help stabilize Algeria’s economy, which is highly dependent on oil revenues and therefore susceptible to outside shocks. The study examines the dynamic relationships between changes (decrease) in the price of crude oil and important macroeconomic indicators, such as GDP, GDP growth, inflation, and remittance factors, using annual data from 1970 to 2023 and a Vector Autoregression (VAR) model. A negative shock to oil prices causes notable contractions in GDP and GDP growth, together with a brief increase in inflation, according to impulse response research. Remittance inflows, on the other hand, rise after such shocks, exhibiting a counter-cyclical trend and underscoring the ability of remittances to mitigate economic downturns. Remittances help to strengthen economic resilience by gradually increasing in importance in the composition of GDP, even though they cannot completely counteract the adverse effects of fluctuations in oil prices. The results highlight how crucial it is to use remittance flows as part of larger plans for economic stability and diversification in rentier nations such as Algeria.